Sporadic colorectal polyps and mismatch repair proteins - Mahsa Molaei; Mahdi Yadollahzadeh; Shohreh Almasi; Sepideh Shivarani; Seyed Reza Fatemi; Mohammad Reza Zali (Wolters Kluwer Medknow Publications, 2011)
Background: Colorectal cancers often arise from benign polyps. Adenomatous polyps and serrated polyps progress step by step to adenocarcinoma and change into malignant cancers. Genetic and epigenetic changes have correlation with specific stages of polyp-adenocarcinoma progression and colorectal cancer histopathological changes. Aims: In this study we used immunohistochemistry (IHC) staining in sporadic colorectal polyps to assay functional status of MLH1, MSH2, MSH6, and PMS2 proteins, to track genetic/epigenetic roles of this issue in our patients. Materials and Methods: In this cross-sectional study we assessed all patients who were admitted with sporadic colorectal polyps and underwent polypectomy in endoscopy department during 2004-2008. Result: IHC results were abnormal in 6.8% cases for MLH1, in 4.5% cases for MSH2, in 3% for MSH6, and in 4.8% for PMS2. In all cases with abnormal PMS2, MLH1 was also reported as abnormal. Same results were reported for abnormal MSH2, which is accompanied with abnormal MSH6 in all cases (P values < 0.001). There is no significant difference between IHC staining results, gender, dysplasia grade, adenomatous type, and invasion. On the other hand, there was significant difference between IHC staining results, polyp location, and mean age of patients. The same significant difference was between adenomatous polyps and serrated adenoma polyps by MLH1 and PMS2 (P values < 0.05). Conclusion: According to our findings, maybe MMR dysfunction is the cause of sporadic colorectal polyps in younger age and its increasing risk of dysplasia progression and malignancy progression is only in serrated adenoma. Sporadic polyps in left colon had a higher risk to progress to malignancies, and abnormal IHC staining for MLH1 and PMS2 in serrated polyps is much more than in other adenomatous polyps.